Smart Wearable Device - Shinde, Aishwarya; Sutar , Samiksha; Hande, Sanskruti; Raut , Sumedha (International Journal of Recent Advances in Engineering and Technology, 2025)
Women’s safety remains a critical issue globally ,with alarming rates of harassment, molestation, and assault reported across various demographics. Despite historical respect for women in society, contemporary challenges persist, with estimates indicating that 35lifetime. To address this pressing issue, this work presents the development of a smart wearable device aimed at enhancing women’s safety through the Internet of Things (IoT). The proposed device is designed for daily use and activates in emergencies to provide real-time protection. Key features include GPS tracking, which allows for continuous location monitoring via a dedicated Android application. Additionally, the device is equipped with an SOS alert system to attract attention from nearby individuals, and it sends SMS notifications to family members and local police stations when activated. This innovative wearable device aims to provide a comprehensive solution to the safety challenges faced by women and improve their overall protection in critical situations.